The DETERMINATION OF THE MANGANESE (MN) CONTENT IN BLACK TEA USING NEUTRON ACTIVATION ANALYSIS - Лувсан, Одонцацрал (Scientific transaction of the National University of Mongolia. Physics, 2025)
In this study, the energy calibration and efficiency of a NaI(Tl) scintillation detector were carried out by activating 55^5555Mn using a 239^239239Pu-Be neutron source within the energy range of 0.5–1.0 MeV. This method was then applied to determine the manganese (Mn) content in several imported black tea samples commonly consumed in Mongolia. The results revealed that the Mn concentration varied depending on the type of tea, ranging from 0.4 to 4.1 mg/g.